An Investigation of How Nitrogen Monoxide (NO) and Nitrogen Dioxide (NO2) Are Produced in Oxidations by Nitric Acid (HNO3). Issue 6 (1st November 2020) - Mousavi, Aliyar
ABSTRACT: In oxidations by nitric acid (HNO3 ), such as the dissolution of gold (Au) in aqua regia, mixtures of nitrogen monoxide (NO) and nitrogen dioxide (NO2 ) are produced. In this article, the exact processes through which these two nitrogen oxides are produced were discussed. It was shown that in the processes of dissolution in HNO3 or aqua regia, NO2 is never a direct product of oxidations by HNO3 . It was also explained that in such processes, NO2 is always produced from HNO3 and NO reacting. Further, the effect of the concentration of HNO3 was discussed in light of thermodynamic calculations. Graphical Abstract: